MAKNA DAN FUNGSI JEMPARINGAN MATARAMAN BAGI ABDI DALEM KARATON NGAYOGYAKARTA HADININGRAT - Paramita, Widyantari Dyah (Institut Seni Indoensia Surakarta, 2020)
Abdi dalem are state servants and cultural servants, who can come from relatives of the palace or from retirees or ordinary people. Ngayogyakarta Palace has a community in preserving culture, one of the community is Gandhewa Mataram community. The Gandhewa Mataram community is focus on preservation of the Jemparingan Mataraman. Pamenthanging gandhewa, pamanthenging cipta is the basis of the philosophy of Jemparingan. It has existed since Hamengkubuwono I. The iconological approach which is part of iconographic theory becomes the method used in analyzing the meaning and function of Jemparingan Mataraman. The data source came from the abdi dalem who participated in the Jemparingan activities. The result of this study stated that the meaning and function of Jemparingan Mataraman were related to the community’s foundation and the life learning process aimed at realizing hamemayu hayuning bawana.Keyword: abdi dalem, jemparingan Mataraman, meaning and function